Eocene granulite-facies metamorphism prior to deformation of the Mianhuadi mafic complex in the Ailao Shan-Red River shear zone, Yunnan Province, SW China. (1st September 2017) - Liu, Ping-Ping; Zhou, Mei-Fu; Zhao, Guochun; Chung, Sun-Lin; Chen, Wei Terry; Wang, Fei
Graphical abstract: Highlights: Eocene granulite-facies metamorphism occurred in the ASRR shear zone prior to shearing. Near-isothermal decompression following the peak metamorphism indicates rapid exhumation. Shearing of the ASRR shear zone has initiated since as early as Late Eocene. Abstract: The Mianhuadi mafic complex in the Ailao Shan-Red River (ASRR) shear zone, SW China, consists of granulite and mylonite, formed by granulite-facies peak metamorphism and retrograde amphibolite-facies metamorphism, with later local mylonitic deformation. Textures and mineral relics indicate that the protolith, represented by the mineral assemblage (M0 ) of olivine, clinopyroxene, plagioclase and Fe-Ti oxides, was emplaced as a mafic intrusion in the Late Permian as part of the Emeishan large igneous province. Two kinds of metamorphic mineral assemblages were identified: the peak assemblage (M1 ) of garnet + orthopyroxene + clinopyroxene + plagioclase + magnetite + ilmenite, and the retrograde assemblage (M2 ) composed of hornblende surrounding orthopyroxene and garnet, and hornblende + spinel symplectite around garnet. Pressure-temperature estimates yield 657–722 °C and 7–9 kbar, and 649–676 °C and 5–6 kbar for the M1 and M2 stages, respectively, roughly defining a clockwise P-T path with near-isothermal decompression following the peak metamorphism. These metamorphic conditions are quite unlike those (pressure up to 14 kbar) of the Late Permian-Middle Triassic metamorphic event in the region. In addition, foliated biotite from mylonites has an 40 Ar- 39 Ar plateau age of 34.3 ± 0.4 Ma, indicating that the ASRR shear zone was active at or before the Late Eocene. Combined with previous data, our new results indicate that the granulite-facies metamorphism of the Mianhuadi mafic complex occurred most likely during the Eocene, followed by rapid exhumation and ductile sinistral shearing in the Late Eocene. The formation of the granulite was likely related to the upwelling of the asthenosphere due to the delamination of overthickened lithospheric mantle after the India-Asia collision.